Conserved sensory-neurosecretory cell types in annelid and fish forebrain: insights into hypothalamus rvolution - Tessmar-Raible, Kristin; Arendt, Detlev (Cell, 2007)
Neurosecretory control centers form part of the forebrain in many animal phyla, including vertebrates, insects, and annelids. The evolutionary origin of these centers is largely unknown. To identify conserved, and thus phylogenetically ancient, components of neurosecretory brain centers, we characterize and compare neurons that express the prohormone vasotocin (vasopressin/oxytocin)-neurophysin in the developing forebrain of the annelid Platynereis dumerilii and of the zebrafish. These neurons express the same tissue-restricted microRNA, miR-7, and conserved, cell-type-specific combinations of transcription factors (nk2.1, rx, and otp) that specify their identity, as evidenced by the specific requirement of zebrafish rx3 for vasotocin-neurophysin expression. MiR-7 also labels another shared population of neurons containing RFamides. Since the vasotocinergic and RFamidergic neurons appear to be directly sensory in annelid and fish, we propose that cell types with dual sensory-neurosecretory properties were the starting point for the evolution of neurosecretory brain centers in Bilateria.